Peran manajemen risiko dalam menghadapi ancaman siber di era digital - Ahmad, Reki (Maliki Interdisciplinary Journal, 2026)
Even though advanced digital technology has made many organisational tasks easier, they are also more vulnerable to cyber threats like malware, data breaches, and peretasan. Because of this situation, organisations need to have a strong risk management system in order to protect information security and operational efficiency. The purpose of this study is to examine how risk management is effective in dealing with cyber threats in the digital age. This research employs a qualitative methodology and does related literary analysis. The results indicate that risk management is crucial for identifying, analysing, and mitigating potential threats through the implementation of safety regulations, the use of pendukung technology, and the enhancement of human sumber daya. Furthermore, the application of frameworks such as ISO 27001 and the NIST Cybersecurity Framework has proven to improve the effectiveness of cyber risk management within organizations. Therefore, the implementation of integrated risk management is a key factor in dealing with the dynamics of cyber threats in the digital era.